2012
DOI: 10.1037/a0028763
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a behavioral economic supplement to brief motivational interventions for college drinking.

Abstract: Objective Behavioral economic theory suggests that a reduction in substance use is most likely when there is an increase in rewarding substance-free activities. The goal of this randomized controlled clinical trial was to evaluate the incremental efficacy of a novel behavioral economic supplement (Substance-Free Activity Session, SFAS) to a standard alcohol brief motivational interviewing (BMI) session for heavy drinking college students. Method Participants were 82 first-year college students (50% female, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
328
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(359 citation statements)
references
References 48 publications
26
328
4
1
Order By: Relevance
“…Extant harm-reduction interventions, such as BASICS (Dimeff et al, 1999), are evidenced to address heavy drinking among college students in general. Further, intervention work has shown that PBS appears to be a relevant component in drinking reduction in this population (Barnett et al, 2007;Larimer et al, 2007;Murphy et al, 2012). Given that individuals experiencing increased mental health symptomatology are at elevated risk for problematic alcohol use, they may benefi t from tailored interventions that emphasize PBS in drinking contexts, particularly during drinking occasions where they experience greater symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant harm-reduction interventions, such as BASICS (Dimeff et al, 1999), are evidenced to address heavy drinking among college students in general. Further, intervention work has shown that PBS appears to be a relevant component in drinking reduction in this population (Barnett et al, 2007;Larimer et al, 2007;Murphy et al, 2012). Given that individuals experiencing increased mental health symptomatology are at elevated risk for problematic alcohol use, they may benefi t from tailored interventions that emphasize PBS in drinking contexts, particularly during drinking occasions where they experience greater symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Brief Alcohol Screening and Intervention for College Students (BASICS; Dimeff et al, 1999), an empirically supported brief motivational drinking intervention, includes PBS to help control one's drinking. College alcohol intervention programs have found that changes in PBS use mediate intervention effects (e.g., Barnett et al, 2007;Murphy et al, 2012). Therefore, the use of PBS appears to be an important component in reducing alcohol-related harms.…”
Section: Protective Behavioral Strategies and Alcohol Usementioning
confidence: 99%
“…For individuals reporting enhancement motives, a more direct focus on the quantity and frequency of their drinking within the context of intervention would seem appropriate. Such drinkers could be provided with alternative behaviors from which to derive positive reinforcement (e.g., Murphy et al, 2012). As an alternative, personalized feedback regarding the types of consequences students have experienced, or might expect to experience given their drinking motives, could be provided.…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence from cross-sectional and longitudinal studies suggests that PBS use is associated with less alcohol use and/or fewer alcohol-related problems (Pearson et al, 2012a). Further, PBS use has also been found to mediate the effects of multiple interventions (Barnett et al, 2007;Larimer et al, 2007;Murphy et al, 2012), providing some evidence that the use of PBS is a proximal mechanism of changing one's alcohol use and related outcomes (Prince et al, 2013). An important next step in PBS research is to determine the extent to which PBS use is one mechanism through which various distal antecedents relate to alcoholrelated outcomes among college students.…”
Section: H Eavy Drinking Among College Studentsmentioning
confidence: 99%